Relación entre el clima institucional y la percepción del desempeño docente en una intitución educativa de Ventanilla - Medina Rondán, Aída Mareli (2010)
The reaserch has the porpuse to know the reasons and the posibilities of better clime institucional and the perceptiòn of the performance teachig This reaser is based in the humanis focusing of Maslow and the aports of Hector Valdes like principal teoric sustents besides we consulted bibliografic source of information. It is a descriptive type of a plan correlative and it applied in one of 50 teachers of secondary land 160 students of fourth and fifth grade of the same level, the instruments. That we applied the were two questionnaires for each variable and the stadistics results maintain demostrate that exists a significant relation between the clime institutional and the performance teacching of our technical educative institution Villa los Reyes of Ventanilla for the development of this present we applied the exam of Spearman and the figures of dispersion.